PENGARUH STRUKTUR MODAL DAN MANAJEMEN LABA TERHADAP PAJAK PENGHASILAN BADAN - Sapta Setia Darma; Euis Nessia Fitri (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
This study aims to examine the effect of Capital Structure and Earnings Management Against Corporate Income Tax. This study uses Corporate Income Tax as the dependent variable and the Capital Structure proxied by Long Term Debt to Asset Ratio (LDAR), Debt to Equity Ratio (DER) and Earnings Management as variables independent. The population in this study are manufacturing companies registered in Indonesia Stock Exchange 2015-2017. This study uses a purposive technique sampling obtained 37 companies that meet the criteria for selecting data samples. Method The analysis used is multiple linear regression analysis, while to measure significant level used partial test (t) and simultaneous test (F). The results of this study shows that partially the Capital Structure proxied by Long Term Debt to Asset Ratio (LDAR) and Debt to Equity Ratio (DER) have an effect on Tax Corporate Income. While earnings management partially has no effect on Corporate Income Tax. Simultaneously Longproxied capital structureterm Debt to Asset Ratio (LDAR), Debt to Equity Ratio (DER) and Earnings Management significant effect on Corporate Income Tax